2014
DOI: 10.1016/j.janxdis.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of post-traumatic stress symptoms in United States Air Force drone operators

Abstract: A B S T R A C TRemotely piloted aircraft (RPA), commonly referred to as "drones," have emerged over the past decade as an innovative warfighting tool. Given there is a paucity of empirical research assessing drone operators, the purpose of this study was to assess for the prevalence of PTSD symptoms among this cohort. Of the 1084 United States Air Force (USAF) drone operators that participated, a total of 4.3% endorsed a pattern of symptoms of moderate to extreme level of severity meeting criteria outlined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 24 publications
4
42
0
5
Order By: Relevance
“…The results of the current study provide information on the prevalence of common mental disorders among US Army aviation personnel and on the percentage of personnel who receive waivers for mental disorders that allow them to return to work and contribute to the aviation mission of the force. The overall prevalence rates for the different disorders based on a diagnosis of the disorder in their medical records were relatively low compared to studies assessing the presence of mental disorders through questionnaire-based assessments (Chappelle et al, 2014;Hoge et al, 2004). Importantly, the current study reflects the prevalence of mental disorders as identified by flight surgeons who are assigned relatively small cohorts of aviation personnel to monitor and evaluate.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The results of the current study provide information on the prevalence of common mental disorders among US Army aviation personnel and on the percentage of personnel who receive waivers for mental disorders that allow them to return to work and contribute to the aviation mission of the force. The overall prevalence rates for the different disorders based on a diagnosis of the disorder in their medical records were relatively low compared to studies assessing the presence of mental disorders through questionnaire-based assessments (Chappelle et al, 2014;Hoge et al, 2004). Importantly, the current study reflects the prevalence of mental disorders as identified by flight surgeons who are assigned relatively small cohorts of aviation personnel to monitor and evaluate.…”
Section: Discussionmentioning
confidence: 89%
“…Aviation personnel in the US Military are frequently required to fly under very difficult operational conditions (Saitzyk, Alfonzo, Greydanus, Reaume, & Parsa, ). Exposure to traumatic events as well as long work hours have been linked to a greater incidence of mental health problems such as post‐traumatic stress disorder (PTSD) among aviation personnel (Chappelle, Goodman, Reardon, & Thompson, ; Dickstein et al, ; Vinokur, Pierce, Lewandowski‐Romps, Hobfoll, & Galea, ). Given the high level of attention, control, and skilled performance necessary to operate complex aircraft, symptoms of mental disorders may compromise the safety and performance of aviation personnel (Saitzyk et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Einsatzgebiete sind sehr vielfältig: Bei der zivilen Nutzung handelt es sich oftmals um die Beobachtung von Infrastrukturen, Grenzen, Verkehr oder um technische Kontrollen (z. B. Hochspannungsmasten) [12], im militärischen Rahmen dienen Drohnen hauptsächlich der Aufklärung beziehungsweise Erkundung sowie der Rettung [13], in speziellen Verwendungsbereichen auch zur Bekämpfung (Kampfdrohnen) von Zielen.…”
Section: Einsatzgebieteunclassified